2004
DOI: 10.1016/j.paerosci.2005.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Review of research into the concept of the microblowing technique for turbulent skin friction reduction

Abstract: A new technology for reducing turbulent skin friction, called the Microblowing Technique (MBT), is presented. Results from proof-of-concept experiments show that this technology could potentially reduce turbulent skin friction by more than 50% of the skin friction of a solid flat plate for subsonic and supersonic flow conditions. The primary purpose of this review paper is to provide readers with information on the turbulent skin friction reduction obtained from many experiments using the MBT. Although the MBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 25 publications
2
24
0
2
Order By: Relevance
“…As is seen, the periodical velocity variation along the plate length plainly correlates with the orifice intervals, which is represented with 250-fold image blowup. Note by the way that, in accordance with the results of direct friction measurement [66], a smaller orifice diameter does not improve the situation. Probably the nonuniform character of the flow at the orifice exit might be partially weakened by a carefully chosen permeable substrate (filter) located immediately below the perforated plate.…”
Section: Characteristics Of the Initial (Unmodified) Flowsupporting
confidence: 70%
See 2 more Smart Citations
“…As is seen, the periodical velocity variation along the plate length plainly correlates with the orifice intervals, which is represented with 250-fold image blowup. Note by the way that, in accordance with the results of direct friction measurement [66], a smaller orifice diameter does not improve the situation. Probably the nonuniform character of the flow at the orifice exit might be partially weakened by a carefully chosen permeable substrate (filter) located immediately below the perforated plate.…”
Section: Characteristics Of the Initial (Unmodified) Flowsupporting
confidence: 70%
“…Ref. [66] presents the aggregation of preliminary Hwang and co-authors' experience; herein, they give the results of the investigations of five perforated plates with thickness from 0.152 to 1.020 mm, porosity varying from 21% to 50% and orifice diameters varying from in 0.06 to 0.381 mm the wind tunnel at Mach numbers from 0.3 to 0.7. The relative mass flow rate of the blown air varied within the range of 0-0.205 kg/m 2 /s.…”
Section: Blowing Through the Wall With Uniformly Distributed Perforatmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies confirmed this possibility, investigating the effects of MBT on more complex geometries as well as on turbulent boundary layers subject to adverse-pressure gradients. For a detailed description of the development of the MBT technique, we refer to the review by Hwang (2004), whereas Kornilov (2015) discusses more recent advancements, focusing on experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Существует множество способов улучшения аэродинамических характеристик летательного аппарата (ЛА), а также отдельных его элементов, в том числе крыла самолета. Некоторые из них основаны на совершенствовании облика ЛА, другие [1][2][3][4] на применении пассивных и активных методов управления пограничным слоем. Проблема состоит в том, что при обтекании многих элементов ЛА, таких как фюзеляж самолета, корпус ракеты, а в некоторых случаях и крыло, пограничный слой в широком диапазоне чисел Рейнольдса находится в турбулентном состоянии.…”
Section: Introductionunclassified